Pengaruh Pengungkapan Praktek Anti Korupsi Pada Sustainability Report Terhadap Going Concern dengan Composite gcg Sebagai Variabel Moderasi (studi kasus pada perbankan indonesia tahun 2015 _ 2018) - IPutu Ariawan; Haryono Umar (Sekolah Pascasarjana Perbanas Jakarta, 2021)
This study was conducted to test and analyze the Effects of Disclosure of Anti-Corruption Practices to Going Concern and the Effects of Composite GCG as Variable Moderation on Disclosure of Anti-Corruption Practices towards Going Concern. This Quantitative research uses secondary data with a total sample of 39 general banking companies listed on the Indonesia Stock Exchange in the period 2015 - 2018 that meet the criteria sample. Data obtained by purposive sampling method. Hypothesis testing using PLS-SEM analysis tools, using Model PLS-SEM with the Moderation Effect Product Indicator Approach contained in the WrapPLS 6.0 Program.The results of this study showed the Disclosure of Anti-Corruption Practices in Sustainability Report had no effect to Going Concern, while the effect of GCG Composite as Variable Moderation weakened the relationship of Disclosure of Anti-Corruption Practices on Sustainability Report towards Going Concern. Good implementation of GCG makes disclosure of Anti-Corruption Practices not a concern for investors in investing